Charged particle production rate from cosmic censorship in dilaton black hole spacetimes - Yen Chin Ong; Yuan Yao (Journal of High Energy Physics, 2019)
Abstract Hiscock and Weems showed that under Hawking evaporation, an isolated asymptotically flat Reissner-Nordström (RN) black hole evolves in a surprising manner: if it starts with a relatively small value of charge-to-mass ratio Q/M, then said value will temporarily increase along its evolutionary path, before finally decreases towards zero. This contrasts with highly charged ones that simply radiate away its charge steadily. The combination of these two effects is the cosmic censor at work: there exists an attractor that flows towards the Schwazschild limit, which ensures that extremality — and hence naked singularity — can never be reached under Hawking evaporation. We apply the scheme of Hiscock and Weems to model the evaporation of an asymptotically flat dilatonic charge black hole known as the Garfinkle-Horowitz-Strominger (GHS) black hole. We found that upholding the cosmic censorship requires us to modify the charged particle production rate, which remarkably agrees with the expression obtained independently via direct computation of charged particle production rate on curved spacetime background. This not only strengthens the case for cosmic censorship, but also provides an example in which cosmic censorship can be a useful principle to deduce other physics. We also found that the attractor behavior is not necessarily related to the specific heat, contrary to the claim by Hiscock and Weems.